Journal of Cultural Management and Cultural Policy / Zeitschrift für Kulturmanagement und Kulturpolitik (transcript-Verlag, 2015)
The Journal of Cultural Management and Cultural Policy is dedicated to international perspectives that address a wide range of issues in cultural management and cultural policy research and practice. It is published twice a year with a thematic section focusing on a special issue and an open section with contributions on varied topics. We invite articles that reflect on organizational structures of creative enterprises, economic and managerial issues in the arts, cultural policy in all its dimensions, as well as creative and aesthetic processes in cultural production, distribution and perception. The journal aims to present multifaceted analysis and rich discourse on current issues in cultural management and cultural policy and to promote the development of research designs and methods relating to both new and established practices in these fields. The journal is open to any theoretical and methodological approach, as long as authors adhere to scholarly rigor. To strengthen the inter- and transdisciplinary character of research in the arts and culture, the journal publishes research articles (6000 to 10.000 words), exploratory essays (about 6.000 words), and case studies (about 4.000 words) from disciplines such as sociology and psychology (of the arts), (cultural) politics, economics, history, cultural theory, philosophy, theatre studies, musicology, and arts education, or the interdisciplinary integration of these. Research articles must fulfill the highest standards in methodological and theoretical approaches; whereas essays give the opportunity to develop a more personal perspective on topics. Case Studies and book reviews complement each issue.